Evaluation of tree tomato genotypes [Cyphomandra betacea (Cav.) Sendt.] for resistance to Phytophthora infestans (Mont.) de Bary sensu lato attacks (2017)
Tree tomato is a species of fruit that is characterized as a production alternative with good acceptance and high demand. However, production has been affected by “gota o tizon tardio”, a disease caused by the oomycete Phytophthora infestans sensu lato. One of the more used methods to control this pathogen in the field is chemicals, but there are efficient and sustainable alternatives that reduce the impact of this disease, such as genetic resistance. The objective of this research was to evaluate 29 tomato genotypes from the departments of Nariño and Putumayo (Colombia) for resistance to attacks from two strains of P. infestans sensu lato, using pathogenicity tests with the in leaf technique, analyzing the parameters: area under the disease progress curve (AUDPC), infection efficiency, lesion size, sporulation rate, and incubation period. When analyzing the results, differences in the behavior of the evaluated genotypes against the attack of the pathogen were found. The genotype G1 was notable because it had the lowest values for AUDPC (15,554), infection efficiency (39%) and lesion size (6.38 cm2), explained by the absence of a genotype-strain interaction and classified as potential for genetic improvement.